What's in the Box? Punishment and Insanity in the Canadian Jury Deliberation Room - Yamamoto, Susan; Maeder, Evelyn M. (Frontiers in Psychology, 2021)
In insanity cases, although the defendant’s eventual punishment is legally irrelevant to the jury’s decision, it may be psychologically relevant. In this three-part mixed-methods study, Canadian jury eligible participants (N = 83) read a fictional murder case involving an insanity claim, then took part in 45-minute deliberations. Findings showed that mock jurors who were generally favorable toward punishment had a lower frequency of utterances that supported the Defence’s case. A qualitative description of keyword flagged utterances also demonstrated that mock jurors relied on moral intuitions about authority, harm, and fairness in justifying their positions. These findings may have application in crafting effective Judge’s instructions and lawyer’s opening statements.